New Putin Presidency’s Foreign Policy: What to Expect - Cheang, Chris (2018)
The contours of Russia’s foreign relations with the West are not expected to change in the next six years, unless a dramatic shift takes place in Russia or the West. However, President Putin is unlikely to worsen the already fraught relationship.